Internet of things-based indoor smart hydroponics farm monitoring system - Yves Lean Krishner Macayana; Ian Christian Fernandez; Kenneth P. Ung; Isabel Austria; Maria Theresa G. De Leon; Chris Vincent J. Densing; John Jairus Eslit; Percival Magpantay; Carlo P. Miras; Darvy Ong; Christopher Santos; Marc Talampas; Nestor C. Michael Tiglao; Marc D. Rosales (Institute of Advanced Engineering and Science, 2023)
Internet of things (IoT)-enabled systems are being used to monitor, control, and optimize agricultural systems like hydroponics. Optimization of these systems requires monitoring of various growth factors for plants which will also require multiple sensors. With the number of wireless sensors needed to track the conditions of the hydroponics system, the wireless sensor network will also grow in size and complexity. In this paper, a hybrid IoT-based monitoring system, with both wired and wireless components, with a target indoor farm application is proposed. The system was implemented using controller area network for the wired component, IPv6 over low power wireless personal area network (6LoWPAN) for the wireless component, and Amazon Web Services for the cloud services. Network simulations were performed to compare the network performance of the proposed hybrid system and the purely wireless system. The simulations show that incorporating a wired system results in improvements such as the reduction of packet loss from 12.23% in the purely wireless system to 5.62% in the hybrid system with burst traffic and even down to 0.0% in the hybrid system with continuous traffic.